What kind of training is required to help language students use metaphor-based strategies to work out the meaning of new vocabulary? - Littlemore, Jeannette (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
A study is described, which compared the benefits of two different training approaches in the use of metaphor-based vocabulary guessing strategies for foreign language learners. A group-based, step-by-step approach was compared with a more autonomous approach. The findings suggest that the type of training received affects the students' ability to use these strategies, but not their tendency to use them. The students who participated in the autonomous approach were significantly more successful at using metaphor-based vocabulary guessing strategies than the students who had received the group training. The difference was particularly marked in terms of their successful use of interactive images.